(untitled) (Revista Sistemas de Producción Agroecológicos, 2011)
To optimize animal production in tropical areas, it is necessary to improve the nutritional quality forage. Besides to maintenance of soil and environmental conditions excellent. The objective was to evaluate the forage potential of five arboreal forages adapted to Meta department of Colombia by testing in vivo digestibility in cattle. Five steers were used with an average weight of 350 ± 18.5 kg, were housed in cages. The treatments were: Grass (Brachiaria decumbens) (T0), five kg of Gliricidia sepium (T1), five kg of Erythrina glauca (T2), five kg of Hibiscus rosa-sinensis (T3), five kg of Trichanthera gigantea (T4) and five kg of Erythrina poeppigiana (T5). The food Consumption, excretion of feces and urine were measured. The digestible energy (DE), metabolic energy (ME), net energy of maintenance (NEm) and net energy of production (NEp) were also calculated. Metabolic cages had feeders, drinkers and mesh floor to collect feces, they had a tilt angle, avoiding contact with urine. In the Animal Nutrition Laboratory analyze to feed and feces: Dry matter (DM), protein, fat, crude fiber (CF), ash, nitrogen free extract (EFN), neutral detergent fiber (NDF) and acid detergent fiber (FDA) to determine digestibility coefficients (cod). The experimental model was a completely randomized design with ten replicates and 6 treatments were applied Tukey tests. The cod of all nutrients were lower in the T0 (P> 0.05), as well as total digestible nutrients (56.4%). H rosa-sinenesis and T gigantea showed the highest digestibility (p<0,05) compared to other treatments. T0 got less (p>0.05) NEp (16.52%), compared to H. rosa-sinenesis (18.77%) T gigantea (18.21%). These two forages showed less losses in feces, urine and metabolic heat. It is concluded that protein and energy are used to a high degree when supplemented with these two forage crops, which shows their excellent nutritional quality.